2020
DOI: 10.3390/cells9040876
|View full text |Cite
|
Sign up to set email alerts
|

Human Peripheral Blood-Derived Endothelial Colony-Forming Cells Are Highly Similar to Mature Vascular Endothelial Cells yet Demonstrate a Transitional Transcriptomic Signature

Abstract: Endothelial colony-forming cells (ECFC) are currently considered as a promising cell population for the pre-endothelialization or pre-vascularization of tissue-engineered constructs, including small-diameter biodegradable vascular grafts. However, the extent of heterogeneity between ECFC and mature vascular endothelial cells (EC) is unclear. Here, we performed a transcriptome-wide study to compare gene expression profiles of ECFC, human coronary artery endothelial cells (HCAEC), and human umbilical vein endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 50 publications
2
32
0
1
Order By: Relevance
“…This indicates the importance of environment on EC gene expression. However, cells do retain some distinguishing factors in vitro, such as intrinsic transcriptional profiles stemming from vascular bed origin and vessel location, which is supportive of a multifactorial process that leads to cell-specific EC transcriptomes (Wick et al, 2007;Burridge and Friedman, 2010;Kutikhin et al, 2020).…”
Section: Innate Contributions To Ec Heterogeneitymentioning
confidence: 99%
“…This indicates the importance of environment on EC gene expression. However, cells do retain some distinguishing factors in vitro, such as intrinsic transcriptional profiles stemming from vascular bed origin and vessel location, which is supportive of a multifactorial process that leads to cell-specific EC transcriptomes (Wick et al, 2007;Burridge and Friedman, 2010;Kutikhin et al, 2020).…”
Section: Innate Contributions To Ec Heterogeneitymentioning
confidence: 99%
“…Recent investigations demonstrated that ECFCs could arise from multiple progenitor cell niches located within the vascular wall of large vessels, including aorta [ 23 ], lung tissue [ 37 ], pulmonary artery [ 38 ], saphenous vein [ 39 ], and placenta [ 40 ], or, they can be obtained from white-adipose tissue [ 41 ] or from human-induced pluripotent stem cells (hiPSCs) sorted for Neuropilin 1 and CD31 [ 42 ]. RNA sequencing confirmed that the gene expression profile of circulating ECFCs was closer to human coronary artery endothelial cells and human umbilical vein endothelial cells as compared to a non-endothelial cell type, such as adipose tissue-derived stromal vascular fraction [ 43 ]. Interestingly, the transcriptomic profile of ECFCs bears more resemblance with that of microvascular, rather than macrovascular, endothelial cells [ 44 ].…”
Section: Endothelial Colony-forming Cells: Origin Mechanisms Of Amentioning
confidence: 99%
“…The hypothesis, that early rabbit EPCs were analyzed here, can be supported by the expression of slightly different phenotype observed in HUVECs (CD14 − CD29 + CD31 + CD34 − CD49f + CD73 + CD90 +/low CD105 + CD133 − CD146 + VE-cadherin + VEGFR-2 + SSEA-4 − vWF + eNOS + AcLDL + ALDH + ), where markers referred to late EPCs (CD31 and CD146) were detected. Recently was demonstrated that human late EPCs possess similar phenotype (CD31 + CD34 − CD45 − CD90 − CD133 − CD146 + VEGFR-2 + vWF + ) as HUVECs [ 26 ]. Hence, although the flow cytometry or immunofluorescence alone is a standard method for the cell phenotyping, inclusion of other methods such as ddPCR is crucial for discovering the true cell phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, the early EPCs are reported to express progenitor markers as CD34 and CD133 as well as VEGFR-2 (Flk-1/KDR), while the late EPCs lose the expression of CD34 and CD133 and express endothelial-associated markers such as von Willebrand factor (vWF), CD31, VE-cadherin (CD144), endothelial nitric oxide synthase (eNOS), VEGFR-2, CD105 and CD146 [ 3 , 5 , 8 , 13 , 20 , 21 , 22 , 23 , 24 , 25 ]. Moreover, the recent study [ 26 ] demonstrated that late EPCs possess similar phenotype (CD31 + vWF + KDR + CD146 + CD34 − CD133 − CD45 − CD90 − ) as human umbilical vein endothelial cells (HUVECs). Interestingly, a transdifferentiation of HUVECs into neuron-like cells was observed under certain culture conditions [ 27 , 28 , 29 ], although there is no information about such differentiation potential of EPCs.…”
Section: Introductionmentioning
confidence: 99%